PERANCANGAN WISATA SAMPAH DENGAN PENDEKATAN ARSITEKTUR EKOLOGI DI RT 02 DAN 03 RW 03 KAMAL, JAKARTA BARAT - Arif Ramadhan Febrianto; Anggraeni Dyah Sulistiowati; Putri Suryandari (MAESTRO, 2020)
Until now, waste is a significant problem in this country. Especially in big cities with a population that exceeds the limit. Therefore it is necessary to make slum prevention efforts, one of which is to maintain environmental quality because the impact that occurs from the influence of environmental quality will also follow the quality of life of the urban community. Waste itself is the most significant problem because it is generally not managed as well as possible, and there is a lack of public awareness and awareness in preserving the environment. Waste that was previously a problem as filth, dirty, smells, causes disease also environmental pollution can become goods that can be utilized and have high economic value. Recycling is one of the methods used to minimize the amount of waste available so that it can increase its economic value into useful items. Waste tourism is a program in which tourists visit a tourist location with the main aim of obtaining direct learning experiences in these tourism objects, in this case, the problem that observes is waste to increase awareness and motivate people's behaviour to care about the environment.